Tuberculosis 2018
DOI: 10.5772/intechopen.76063
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Tuberculosis

Abstract: Urinary tract tuberculosis (UTTB) is an insidious disease with non-specific constitutional symptoms that are often unrecognized and lead to delayed diagnosis. Advanced UTTB may cause loss of kidney function. In the majority of literature, UTTB is reviewed together with genital tuberculosis because often both sites are involved simultaneously; "Genitourinary tuberculosis" (GUTB) is the most common term used in the literature. However, the term may cause confusion because the clinical presentation and diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 112 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…Most patients with B B renal TB have sterile pyuria, which can be as a result of microscopic hematuria in the absence of a common bacterial infection. 6 The diagnosis of tuberculosis is formulated based on medical history, clinical signs, instrumental examinations, and the search for the Koch bacillus in lung sputum, pleural fluid, urine, cerebrospinal fluid, lymph node biopsies, cytology, PCR for TB, etc. CT abnormalities reported from renal tuberculosis CT features are varied and depend upon the stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with B B renal TB have sterile pyuria, which can be as a result of microscopic hematuria in the absence of a common bacterial infection. 6 The diagnosis of tuberculosis is formulated based on medical history, clinical signs, instrumental examinations, and the search for the Koch bacillus in lung sputum, pleural fluid, urine, cerebrospinal fluid, lymph node biopsies, cytology, PCR for TB, etc. CT abnormalities reported from renal tuberculosis CT features are varied and depend upon the stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]7,8 Huang et al, and few other studies stated that the kidney is the most common site infected in GUTB infection. 1,3,11,12 Eastwood et al in their research found that epididymis and prostate were the most common site being infected in men. 9 In our research, we find that the bladder was the site that was most infected (36.4%), followed by ureter and prostate (18.9%), respectively.…”
Section: Discussionmentioning
confidence: 99%